Surface deformation and ferroelectric domain switching induced by a force microscope tip on a La-modified PbTiO3 thin film - Labardi, M.; Polop, C.; V. Likodimos; Pardi, L.; Allegrini, M.; Vasco, E.; Zaldo, C. (Applied Physics Letters, 2003)
Surface deformation and ferroelectric domain switching induced by a force microscope tip on a La-modified PbTiO3 thin film was studied. Polarization switching of the domains comprising the deformed region demonstrated the possibility of using scanning force microscopy (SFM) as a nanoscale tool for imaging phase transitions. It was found that if loading forces are higher than a threshold value, thin film characterization becomes invasive.